A Comprehensive Study on Dielectric Properties of Volcanic Rock/PANI Composites - Kilic, M.; Karabul, Y.; Okutan, M.; Icelli, O. (IOP PUBLISHING LTD, 2016)
Basalt is a very well-known volcanic rock that is dark colored and relatively rich in iron and magnesium, almost located each country in the world. These rocks have been used in the refused rock industry, to produce building tiles, construction industrial, highway engineering. Powders and fibers of basalt rocks are widely used of radiation shielding, thermal stability, heat and sound insulation. This study examined three different basalt samples (coded CM-1, KYZ-13 and KYZ-24) collected from different regions of Van province in Turkey. Polyaniline (PANI) is one of the representative conductive polymers due to its fine environmental stability, huge electrical conductivity, as well as a comparatively low cost. Also, the electrical and thermal properties of polymer composites containing PANI have been widely studied. The dielectric properties of Basalt/Polyaniline composites in different concentrations (10, 25, 50 wt.% PANI) have been investigated by dielectric spectroscopy method at the room temperature. The dielectric parameters (dielectric constants, loss and strength) were measured in the frequency range of 10(2) Hz-10(6) Hz at room temperature. The electrical mechanism change with PANI dopant. A detailed dielectrically analysis of these composites will be presented.
Keywords: DISPERSION; Physics